A Case Study on Caustic Corrosion in Refinery Piping (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Caustic soda is received from supplier with concentration about 48% and stored at main storage tank and transferred intermittently to the refinery process unit's neutralization tanks at same concentration. Dilution is taking place at these tanks. In order to prevent caustic soda from freezing and /or crystallization (winterization) in intermittent transferring piping, it was kept warm by means of steam tracing and insulation together.Failure of carbon steel piping by caustic stress corrosion cracking (embrittlement) and caustic gouging has been a recurring problem, several repairs attempts were made without success using patch plates and/or temporary clamps. Some parts were totally replaced with schedule 80 piping but suffer failures within 12 months.Close observation of the corroded locations reveals severe grooving along the length of pipe at 3 & 9 o'clock positions where steam tracing line is touching the pipes due to braking of fixation clamps.Several measures were recommended, these include avoidance of hot spots by steam tracing; avoidance of temperature increase during idle condition and redesigning the distribution piping in order to transfer caustic solution with concentration not more than (33%).